2016
DOI: 10.18869/acadpub.jafm.68.236.25247
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of Boundary Layer Flow over a Moving Plate in a Nanofluid with Viscous Dissipation

Abstract: In this study, the numerical investigation of boundary layer flow over a moving plate in a nanofluid with viscous dissipation and constant wall temperature is considered. The governing non-linear partial differential equations are first transformed into a system of ordinary differential equations using a similarity transformation. The transformed equations are then solved numerically using the Keller-box method. Numerical solutions are obtained for the Nusselt number, Sherwood number and the skin friction coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Saritha et al [15] performed the heat transfer analysis of boundary layer flow of power law fluid with viscous dissipation. Mohamed et al [16] numerically studied the effects of viscous dissipation on a flow of nanofluid over a moving flat plate. Some recent studies on the heat transfer analysis with and without viscous dissipation effects are reported in [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Saritha et al [15] performed the heat transfer analysis of boundary layer flow of power law fluid with viscous dissipation. Mohamed et al [16] numerically studied the effects of viscous dissipation on a flow of nanofluid over a moving flat plate. Some recent studies on the heat transfer analysis with and without viscous dissipation effects are reported in [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Brownian motion Nb and thermophoresis parameter Nt are tackled over the temperature profile. For validation purposes, the comparison among the present study with the earlier publications reported by Roşca and Pop [10] and Mohamed et al [11] is carried out for several values of Pr , i.e. Pr 0.7, 0.8, 1, 5, 10  .…”
Section: Resultsmentioning
confidence: 90%
“…Apparently, the numerical values in table 1 are excellently closed to each other; hence, the numerical code utilised throughout this study is concluded to effectually solve the current problem. Referring to Mohamed et al [11,16], Pr 7  is used for the current numerical simulations as it represents water that usually acts as the base fluid for nanofluid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the rate of heat transfer decreased and mass transfer rate increased with increasing viscous dissipation parameter true(Ectrue). Mohamed et al showed that with the increase in Ec , the thermal boundary layer thickness also increased in the study of boundary layer flow over a moving plate with the presence of viscous dissipation and constant wall temperature for nanofluids. Vajravelu et al studied the effects of surface mass transfer and thermal radiation on the flow field generated by a shrinking sheet in the presence of viscous dissipation and radiation.…”
Section: Introductionmentioning
confidence: 99%